Potensi Metabolit Kapang Endofit Mangrove Rhizophora apiculata sebagai Anti-Staphylococcus epidermidis - Limbong, Maria Fransiska; Setyati, Wilis Ari; Sedjati, Sri; Sibero, Mada Triandala (Universitas Diponegoro, 2024)
Mangrove association molds are known to produce secondary metabolite compounds that have antibacterial activity. The purpose of this study was to obtain anti-Staphylococcus epidermidis metabolites produced by the endophytic mold of mangrove Rhizophora apiculate. The screening process is carried out in exploratory descriptive research. The stages of this research are sampling, mold isolation and purification, and macroscopic characterization. Initial screening of antibacterial activity is carried out by the agar plug method. Isolates that produce antibacterial metabolites are molecularly identified. The isolate was then cultured with Potato Dextrose Agar (PDA) media. The producing antibacterial metabolites were extracted using two solvents of different polarities (ethyl acetate and methanol) by stratified maceration method. Antibacterial metabolites are then tested to determine the concentration of extracts required to inhibit (Minimum Inhibitory Concentration (MIC) and kill bacterial growth (Minimum Bactericidal Concentration / MBC). The results of this study showed that there is one species of mangrove endophytic mold Rhizophora apiculata that can produce antibacterial metabolites against S. epidermidis, namely Diaporthe sennae. These antibacterial metabolites are present in ethyl acetate extract. The resulting bioactivity based on the ability to inhibit bacterial growth can be seen from the MIC value of 2.5 mg / mL and the ability to kill bacteria with an MBC value of 5 mg / mL. The mold metabolite Diaporthe sennae could potentially be developed as an anti-Staphylococcus epidermidis Kapang asosiasi mangrove diketahui menghasilkan senyawa metabolit sekunder yang memiliki aktivitas antibakteri. Tujuan penelitian ini adalah untuk mendapatkan metabolit anti-Staphylococcus epidermidis yang dihasilkan oleh kapang endofit mangrove Rhizophora apiculate. Proses skrining dilakukan secara diskriptif eksploratif. Tahapan penelitian ini adalah pengambilan sampel, isolasi dan purifikasi kapang, serta karakterisasi makroskopis. Skrining awal aktivitas antibakteri dilakukan dengan metode agar plug. Isolat yang menghasilkan metabolit antibakteri diidentifikasi secara molekuler. Isolat tersebut selanjutnya dikultur dengan media Potato Dextrose Agar (PDA). Metabolit antibakteri yang dihasilkan diekstraksi menggunakan dua pelarut yang berbeda polaritas (etil asetat dan metanol) dengan metode maserasi bertingkat. Metabolit antibakteri kemudian diuji untuk menentukan konsentrasi ekstrak yang diperlukan untuk menghambat (Minimum Inhibitory Concentration /MIC) dan membunuh pertumbuhan bakteri (Minimum Bactericidal Concentration /MBC). Hasil penelitian ini menunjukkan bahwa terdapat satu spesies kapang endofit mangrove Rhizophora apiculata yang yang dapat menghasilkan metabolit antibakteri melawan S. epidermidis, yaitu Diaporthe sennae. Metabolit antibakteri tersebut terdapat dalam ekstrak etil asetat. Bioaktivitas yang dihasilkan berdasarkan kemampuan menghambat pertumbuhan bakteri terlihat dari nilai MIC sebesar 2,5 mg/mL dan kemampuan membunuh bakteri dengan nilai MBC sebesar 5 mg/mL. Metabolit kapang Diaporthe sennae berpotensi dikembangkan sebagai anti-Staphylococcus epidermidis